2019
DOI: 10.1371/journal.pone.0225929
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and mineral composition of weathered serpentine rock of the Khalilovsky massif

Abstract: Endolithic microbial communities survive nutrient and energy deficient conditions while contributing to the weathering of their mineral substrate. This study examined the mineral composition and microbial communities of fully serpentinized weathered rock from 0.1 to 6.5 m depth at a site within the Khalilovsky massif, Orenburg Region, Southern Ural Mountains, Russia. The mineral composition includes a major content of serpentinite family (mostly consisting of lizardite and chrysotile), magnesium hydrocarbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…The relative abundances of Actinobacteria, FBP, and Deinococcus-Thermus were also higher in the lithic communities. The order Solirubrobacterales in Actinobacteria were the most abundant group observed in lithic niches, consistent with previous studies that have been observed in rocks ( Esposito et al, 2015 ; Khilyas et al, 2019 ). The 16S rRNA sequence of candidate division FBP was first reported from a lichen-dominated lithic habitat in Antarctica ( de la Torre et al, 2003 ), and Deinococcus-Thermus was also dominant in cryptoendolithic environments ( Cary et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…The relative abundances of Actinobacteria, FBP, and Deinococcus-Thermus were also higher in the lithic communities. The order Solirubrobacterales in Actinobacteria were the most abundant group observed in lithic niches, consistent with previous studies that have been observed in rocks ( Esposito et al, 2015 ; Khilyas et al, 2019 ). The 16S rRNA sequence of candidate division FBP was first reported from a lichen-dominated lithic habitat in Antarctica ( de la Torre et al, 2003 ), and Deinococcus-Thermus was also dominant in cryptoendolithic environments ( Cary et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Another active actinobacterial group abundant in these soils, order Solirubrobacterales, is not well characterized. These are mesophilic heterotrophs and based on 16S rRNA gene analysis, Solirubrobacterales have been encountered in diverse environments, such as weathered serpentine rock (Khilyas et al ., 2019), Antarctic soil (Chong et al ., 2012), agroecosystem soils (Shange et al ., 2012), Sphagnum peat bog (Ivanova et al ., 2016), and shrub-associated desert soil (Saul-Tcherkas & Steinberger, 2011). This wide range of habitats suggests that this order includes mixotrophic bacteria with the ability to survive in environments with fluctuating conditions, including temperature, nutrients, and UV radiation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Anaerolineaceae (the keystone taxa in one module uncorrelated with the measured enzymes) have been found to participate into methanogenesis (Liu et al ., 2020a). Also, Solirubrobacterales were largely detected in weathered serpentine rock, which implied a potential mineral cycling capacity (Khilyas et al ., 2019). Regardless, distributed ecosystem functions across soil microorganisms can increase the stability and sustainability of arable soils (Rolland et al ., 2012; Bhatt et al ., 2016), which is supported by the high stability of the community in the paddy agroecosystem (Table 5).…”
Section: Discussionmentioning
confidence: 99%